Expertise and processing distorted structure in chess - Bartlett, James; Boggan, Amy L.; Krawczyk, Daniel C. (Frontiers in Human Neuroscience, 2013)
A classic finding in research on human expertise and knowledge is that of enhanced memory for stimuli in a domain of expertise as compared to either stimuli outside that domain, or within-domain stimuli that have been or degraded or distorted in some way. However, we do not understand how the expert brain processes within-domain stimuli that have been distorted enough to be perceived as impossible or wrong, and yet still are perceived as within the domain (e.g., a face with the eyes, nose and mouth in the wrong positions, or a chessboard with pieces placed randomly on the board). Focusing on the domain of chess, we present new fMRI evidence that when experts view such distorted/within-domain stimuli, they engage an active search for structure – a kind of exploratory chunking – that involves a component of a prefrontal-parietal network linked to consciousness, attention and working memory.